Diagnosis dan Tatalaksana Epilepsi - Fitriyani Fitriyani; putri puspa devi; Ria Wahyu Januarti (Medula, 2023)
Epilepsy is defined as a brain disorder characterized by a tendency to cause continuous epileptic seizures with neurobiological, cognitive, psychological, and social consequences. The definition of epilepsy requires at least one epileptic seizure. In developing countries, the incidence of epilepsy is 61-124/100,000 children per year. The prevalence of epilepsy cases in Indonesia is 8.2 per 1,000 population with an incidence rate of 50 per 100,000 population. This study aims to systematically establish a diagnosis in a 42-year-old male patient so that the patient can be treated appropriately. The method used is case report with primary data analysis obtained through autoanamnesis, alloanamnesis, physical examination and supporting examination. A 42-year-old man came with complaints of recurrent seizures, a systematic anamnesis and physical examination were carried out to establish an etiologic diagnosis. The patient in this case was diagnosed with epilepsy. The patient in this case was diagnosed with epilepsy. The management given to this patient consisted of general management in the form of bed rest accompanied by monitoring of the patient's vital signs, and given medical therapy in the form of RL infusion XV gtt/min, gluconas ca drip/8 hours, KSR 3x1 tab, KCL drip 1 fls/8 hours, Phenytoin 1 ampoule/8 hours in 100 cc normosaline, and Folic Acid 2x1. To further support the diagnosis, the patient was advised to do an EEG examination.